Lymphatic Filariasis: Epidemiological Analysis of the Situation in Salyantar VDC of Dhading District, Nepal - Byanju, Reena; Gupta, Ranjana (Journal of Natural History Museum, 2015)
A cross sectional survey was carried out by taking 516 mid night blood samples from 206 households in 1,2 and 3 wards of Salyantar village development committee of Dhading district, Nepal with the objective to analyze the epidemiological situation of lymphatic filariasis. The main aim of the study was to provide the data essential for the planning, implementation and evaluation of the services to the prevention, control and treatment of lymphatic filariasis. Questionnaire survey was conducted for the collection of information of the respondents. Blood samples were collected by means of ear-lobe prick method. Microscopical examination of the collected blood samples revealed 117 positive cases i.e. 22.67%. Males (24.54%) were found to be infected more than females (21.28%) in the ration of 1.2:1. The highest distribution of microfilarial parasites was in the age group >70 years (36.36%) while the least was in the age group ≤10 years (12.37%). The infected youngest person was 4 years old boy and the oldest was 85 years old man. Endemicity rate and crude disease rate was reported to be 44.76% and 22.09% respectively. Illiteracy, lack of awareness about the disease, poor sanitation, carelessness in using bed-nets and health were identified as the major risk factors for filariasis. J. Nat. Hist. Mus. Vol. 26, 2012: 136-145